2021
DOI: 10.1186/s12883-021-02232-6
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis in a South Asian population

Abstract: Background Autoimmune encephalitis (AE) is now considered a main, potentially curable cause of encephalitis, but remains conspicuously underreported from South Asia. We studied the clinical characteristics in relation to their antibody status and outcomes of patients presenting with AE in Sri Lanka. Methods Patients admitting to government hospitals who were clinically suspected of AE by an on-site neurologist were prospectively recruited over a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…The sensitivity of the proNMDARE criteria ( 4 ) was 0.67 in our cohort, as three of nine patients with NMDARE were false negatives. This value was consistent with that of other cohort studies (approximately 0.70) ( 5 , 12 14 ). However, the method using an FSR cutoff value salvaged the three patients who did not meet proNMDARE criteria, thereby achieving a sensitivity of 1.00 ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The sensitivity of the proNMDARE criteria ( 4 ) was 0.67 in our cohort, as three of nine patients with NMDARE were false negatives. This value was consistent with that of other cohort studies (approximately 0.70) ( 5 , 12 14 ). However, the method using an FSR cutoff value salvaged the three patients who did not meet proNMDARE criteria, thereby achieving a sensitivity of 1.00 ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Antibodies that flock to neuronal surface antigens trigger both paraneoplastic and non-paraneoplastic AE, which includes a variety of inflammatory brain disorders (2), accounting for 21%-39% of acute encephalitis (10)(11)(12). Since Graus et al ( 4) developed an algorithm for the diagnosis of AE, which consisted of syndrome-based approach and antibody testing, several studies have been reported that classified the encephalitis cohort into specific conditions of autoimmune etiology by the criteria (5,(12)(13)(14). Given that the AE defined by the criteria is not a single disease entity, it is no wonder the proportion of each specific condition is varied among the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in this study AE was diagnosed in only 2% of unselected encephalitis patients, a recent study which selected patients with suspected AE based on established diagnostic criteria[ 11 ] found up to 50% of patients to have AE and 44.6% of them to have detectable pathogenic antibodies to recognized AE in CSF. [ 5 ] The higher yield in the cited study is likely due to exclusion of patients with likely infectious etiologies, which probably accounts for most of the encephalitis in regions with a high prevalence of infections.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] In temperate regions, the incidence and prevalence of AE has been reported to be comparable to viral encephalitis. [ 4 ] However, research on AE from South Asia remains sparse,[ 5 ] but infectious etiologies are assumed to predominate. [ 6 ] Although neuronal autoantibodies can occur as para- or post-infectious epiphenomena, only about one-third would result in AE.…”
Section: Introductionmentioning
confidence: 99%